Recent Answers to Farmland Degradation Illustrated by Case Studies from African Farming Systems - Stigter, C J; Oteng, S B B; Ohuwasemire, K O; Asar Al-amin, N K; Kinama, J M; Onyewotu, L O Z (Annals of Arid Zone, 2016)
Farmland of relatively marginal Low Extemal Input Sustainable Agriculture (LEISA) famlers in developing countries is prone to degradation from various local environmental and management causes. In the Traditional Techniques of Microclimate Improvement (TTMI) project in Africa, several such causes were (proposed to be) counteracted with relatively simple means available or made available to such farmers. Examples of causes and answers illustrated in this paper have to do with degradation of often marginal soils caused by migration (central Kenya), by low soil cover, low nutrient status and low water holding capacity in intercropping (northem Nigeria), by wind erosion and desertification threatening irrigated land and its protection (central Sudan), by water-caused soil erosion and runoff on sloping land (eastem Kenya) and by deforestation and heat advection negatively affecting soil moisture and crops (Sahelian Nigeria). Each of the above examples of farmland degradation is closed by summarizing what we leamed as answers. In these answers, small to medium scale agrometeorological and agroclimatological management, in many cases including the agroforestry use of non-forest trees for protection purposes, play an important role. It is concluded that in LEIS A, contemporary science improving traditional approaches and supporting local innovations, should be assisted by appropriate policy environments to produce relevant services for farmers in sufficient numbers and on a sufficient scale. In this context it should always be local windows of opportunity for LEISA farmers that have to be researched in a participatory approach to combat land degradation.